Assessing caseworker perceptions of client engagement in Danish child and family welfare - Pontoppidan, Maiken; Rayce, Signe Boe (Frontiers in Sociology, 2025)
Engagement, defined as the quality of the collaborative relationship between social workers and families, is fundamental to effective statutory social work. A key aspect of worker engagement is how caseworkers perceive client engagement, as these perceptions shape their approach to collaboration, influence decision-making, and ultimately impact service delivery and case outcomes. Understanding and assessing perceived client engagement can help caseworkers strengthen relationships despite the inherent power imbalances and challenges of non-voluntary settings. This paper presents the development of a questionnaire with 23 questions designed to assess caseworker perceptions of client engagement within Denmark’s child and family welfare system. Analysis of responses from 35 caseworkers indicated that most families were perceived as actively engaged and collaborative, with 21 out of 23 questions showing a median score of 4 on a 1–5 scale. Responses for 20 questions covered the full range of response categories, though extreme categories were less frequently used. Interviews with caseworkers suggested that the questionnaire also served as a valuable reflective tool, encouraging them to critically assess their professional relationships and engagement strategies. While initial findings support the questionnaire’s usability, validation studies are needed to evaluate its psychometric properties. Such studies could enhance its value both as a measure of engagement and as a tool for supporting reflective practice in child and family welfare contexts.